Dottoro Exploring Factors Influencing Equitable Access to Healthcare in Urban Makassar through the Dottoro’ta Case: English - Razak, Amran (Balai Besar Pelatihan Kesehatan (BBPK) Makassar, 2024)
Background : Efforts to increase equitable access to health services require innovative interventions and institutional strengthening. Maintaining equal and fair access requires transformative changes in health care interventions. This research aims to identify potential factors for the Dottoro'ta home care program as an innovative intervention to provide equal and inclusive access to health services in Makassar City. Method : This study uses qualitative research to identify potential factors in the Dottoro'ta home care program in primary health services in urban areas. Potential factors include identifying assets needed for homecare services, detecting the need for homecare services based on economic and social factors, formulating innovative, equal and sustainable homecare service models in urban areas. Data collection was carried out through semi-structured in-depth interviews with program managers, and health officers implementing the program, as well as people who had used Dottoro'ta services (n=29). Thematic analysis was conducted to examine important themes that emerged. Results : The findings of this study indicate that potential components play an important role in supporting the Dottoro'ta home care program, given limited resources. This research found that the Dottoro'ta program is a cost-effective health service approach and can reduce gaps in the implementation of the Social Security Administering Agency (BPJS) in the health sector, and is easy to replicate in the provision of primary health services. Conclusion : These findings highlight the extent to which the potential role of the Dottoro'ta home care program in urban areas with limited resources can address health care disparities. The adaptability and cost effectiveness of the Dottoro'ta program is an ideal solution in providing primary health services, especially in urban areas where health services are still difficult to reach. Keywords : home care service, equitable access, innovation intervention.